2016
DOI: 10.3382/ps/pev209
|View full text |Cite
|
Sign up to set email alerts
|

Housing conditions alter properties of the tibia and humerus during the laying phase in Lohmann white Leghorn hens

Abstract: Osteoporosis in caged hens is one driving factor for the United States egg industry to explore options regarding alternative housing systems for laying hens. The aim of our research was to study the influence of housing systems on tibiae and humeri of 77-week-old Lohmann White hens. Pullets raised in an aviary system were either continued in aviary hen systems (AV) or conventional cages (AC) whereas pullets reared in conventional cages continued in conventional hen cages (CC) or enriched colony cages (EN) at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…The improved bone mechanical properties of aviary birds should be directly related to greater physical activity of these birds in this type of housing (Fleming et al, 2006) which have been confirmed during lay (Leyendecker et al, 2001;Regmi et al, 2016) and during rear (Regmi et al, 2015). Prolonged immobility in cage hens increases bone resorption whereas increased physical activity (as in aviary birds) stimulate bone formation and remodeling.…”
Section: Discussionmentioning
confidence: 84%
“…The improved bone mechanical properties of aviary birds should be directly related to greater physical activity of these birds in this type of housing (Fleming et al, 2006) which have been confirmed during lay (Leyendecker et al, 2001;Regmi et al, 2016) and during rear (Regmi et al, 2015). Prolonged immobility in cage hens increases bone resorption whereas increased physical activity (as in aviary birds) stimulate bone formation and remodeling.…”
Section: Discussionmentioning
confidence: 84%
“…Bending moment can be described as a yield load adjusted to the bone length and it indicates bone elastic load capability [30]. The elastic stress reflects the elastic strength of midshaft cortical bone, the ultimate stress is equal to the maximum stress a bone can withstand in bending before fracture [30, 31]. …”
Section: Methodsmentioning
confidence: 99%
“…111 There are also differences in leg bone characteristics with hens under the cage free conditions having increased cortical cross-sectional area and cortical density of their humerus and tibia compared to those maintained in conventional cages. 112 Moreover, there was there was greater stiffness of both humerus and tibia and increased percentage ash in the humerus in hens in a cage free system. 112,113 However, in another study, there were little differences between tibia and humerus parameters between hens in cage-free or conventional cage systems.…”
Section: Approaches To Reduce Broodinessmentioning
confidence: 91%
“…112 Moreover, there was there was greater stiffness of both humerus and tibia and increased percentage ash in the humerus in hens in a cage free system. 112,113 However, in another study, there were little differences between tibia and humerus parameters between hens in cage-free or conventional cage systems. 111 In laying hens at the end of the laying cycle, there were differences in bone characteristics depending on the environment under which the pullets were raised.…”
Section: Approaches To Reduce Broodinessmentioning
confidence: 91%
See 1 more Smart Citation